A case-study evaluation of the “Copenhagen Music Program” for psilocybin-assisted therapy - Ratkovic, Gina; Sosteric, Mike; Sosteric, Tristan (Frontiers in Psychology, 2023)
In a recent article, Messell and colleagues provide a curated list, the “Copenhagen Music Program for Psilocybin”. We test their music program with an experienced Indigenous therapist/psychonaut on a 3.5 gram psilocybin journey. Based on comments provided by the Indigenous therapist, we find the program contains musical choices that evoke specific colonial and religious contexts. We also find the program psychologically and emotionally coercive, meaning it is intended to contain the experience by forcing the individual on a specific experiential pathway. We conclude the program is not suitable for Indigenous travelers and suggest that curation of a wider variety of playlists, and music more in line with traditional shamanic practices, might be a better approach to psychedelic curation.